Penerapan Model Group Investigation (GI) dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam: Implementation of the Group Investigation (GI) Model to Enhance Islamic Religious Education Learning Outcomes - Hafizia Haryanto, Friska; Aliyah, Adah; Rosadi, Adi; Marwiji, Muh. Hasan (Sekolah Tinggi Agama Islam Kharisma Cicurug Sukabumi, 2024)
This study examines the low learning outcomes in Islamic Education (PAI) among 11th-grade Science 1 students at SMA Negeri 1 Cidahu, caused by conventional, non-interactive teaching methods that reduce motivation and engagement. Many students fail to meet the Minimum Competency Standards (KKM) due to passive learning. To address this, the research evaluates the effectiveness of the Group Investigation (GI) cooperative learning model in improving student participation and understanding, particularly on the topic